Cloning of the GABAB Receptor Subunits B1 and B2 and their Expression in the Central Nervous System of the Adult Sea Lamprey - Romaus-Sanjurjo, Daniel; Fernández-López, Blanca; Sobrido-Cameán, Daniel; Barreiro-Iglesias, Antón; Rodicio, María Celina (Frontiers in Neuroanatomy, 2016)
In vertebrates, γ-aminobutyric acid (GABA) is the main inhibitory transmitter in the central nervous system acting through ionotropic (GABAA) and metabotropic (GABAB) receptors. The GABAB receptor produces a slow inhibition since it activates second messenger systems through the binding and activation of guanine nucleotide-binding proteins [G-protein-coupled receptors (GPCRs)]. Lampreys are a key reference to understand molecular evolution in vertebrates. The importance of the GABAB receptor for the modulation of the circuits controlling locomotion and other behaviors has been shown in pharmacological/physiological studies in lampreys. However, there is no data about the sequence of the GABAB subunits or their expression in the central nervous system (CNS) of lampreys. Our aim was to identify the sea lamprey gabab1 and gabab2 transcripts and study their expression in the CNS of adults. We cloned two partial sequences corresponding to the gabab1 and gabab2 cDNAs of the sea lamprey as confirmed by sequence analysis and comparison with known gabab sequences of other vertebrates. In phylogenetic analyses, the sea lamprey GABAB sequences clustered together with GABABs sequences of vertebrates and emerged as an outgroup to all gnathostome sequences. We observed a broad and overlapping expression of both transcripts in the entire CNS. Expression was mainly observed in neuronal somas of the periventricular regions including the identified reticulospinal cells. No expression was observed in identifiable fibers. Comparison of our results with those reported in other vertebrates indicates that a broad and overlapping expression of the GABAB subunits in the CNS is a conserved character shared by agnathans and gnathostomes.